Documenting relations between requirements and design decisions: a case study on design session transcripts - Hesse, Tom-Michael; Paech, Barbara (Requirements Engineering: Foundation for Software Quality, 2016)
Context/Motivation: Developers make many important decisions as they address given requirements during system design. Each decision is explained and justified by decision-related knowledge. Typically, this knowledge is neither captured in a structured way, nor linked to the respective requirements in detail. Then, it is not obvious, how design decisions realize the given requirements and whether they further refine or shape them. Thus, the relations and alignment of requirements and design cannot be assessed properly. Problem/Question: While there are several studies on decision-making in general, there does not exist a study uncovering how decision-related knowledge emerges based on requirements. Such a study is important to understand the intertwined relations of requirements and design decisions as well as how requirement descriptions could be enhanced with feedback from design decision-making. Principal Idea/Results: We applied a flexible documentation approach for decision-related knowledge on discussion transcripts of two design sessions with professional designers. We analyzed the discussions for decision-related knowledge and documented it together with its relations to the given requirements. Several complex and incrementally growing knowledge structures for decisions were found to emerge in relation to the given requirements. Also, we uncovered that decision-related knowledge contained uncertainties about requirements and further refined them. Contribution: Our study uncovers detailed relations between requirements and design decisions and thereby improves the understanding of their mutual impact on each other. We also derive recommendations for the cooperation between requirements engineers and designers in practice. In addition, we demonstrate that our documentation approach for decision-related knowledge provides a comprehensive view on decisions and their relations to requirements.